Biomechanical behavior of overdentures supported by different implant position and angulation using Micro ERA® system - Felipe Franco Ferreira; Guilherme Almeida Borges; Letícia Del Rio Silva; Daniele Valente Velôso; Thaís Barbin; Marcelo Ferraz Mesquita (Brazilian Journal of Oral Sciences, 2019)
Aim: The aim of this study was to investigate the biomechanical behavior of implant-retained mandibular overdentures using Micro ERA® system with different implant position and angulation by finite element analysis (FEA). Methods: Four 3D finite element models of simplified mandibular overdentures were constructed, using one Bränemark implant with a Micro ERA® attachment. The implant was positioned on the canine or lateral incisor area with an angulation of either 0º (C-0º; LI-0º) or 17º (C-17º, LI-17º) to the vertical axis. A 100 N axial load was applied in one side simultaneously, from first premolar to second molar. In all models it was analyzed the overdenture displacement, compressive/tensile stress in the bone-implant interface, and also the von Mises equivalent stress for the nylon component of the housing. The stresses were obtained (numerically and color-coded) for further comparison among all the groups. Results: The displacement on the overdenture was higher at the posterior surface for all groups, especially in the C-17º group. When comparing the compressive/tensile stress in the bone-implant interface, the lateral-incisor groups (LI-0º and LI-17º) had the highest compressive and lowest tensile stress compared to the canine groups (C-0º and C-17º). The von Mises stress on the nylon component generated higher stress value for the LI-0º among all groups. Conclusions: The inclination and positioning of the implant in mandibular overdenture interferes directly in the stress distribution. The results showed that angulated implants had the highest displacement. While the implants placed in the lateral incisor position presented lower compressive and higher tensile stress respectively. For the attachment the canine groups had the lowest stress.